Digital Mis/Disinformation and Public Engagement with Health and Science Controversies: Fresh Perspectives from Covid-19 - Nguyen, An (2020)
Digital media, while opening a vast array of avenues for lay people to effectively engage with news, information and debates about important science and health issues, have become a fertile land for various stakeholders to spread misinformation and disinformation, stimulate uncivil discussions and engender ill-informed, dangerous public decisions. Recent developments of the Covid-19 infodemic might just be the tipping point of a process that has been long simmering in controversial areas of health and science (e.g., climate-change denial, anti-vaccination, anti-5G, Flat Earth doctrines). We bring together a wide range of fresh data and perspectives from four continents to help media scholars, journalists, science communicators, scientists, health professionals and policy-makers to better undersand these developments and what can be done to mitigate their impacts on public engagement with health and science controversies.